Headache in ADHD as comorbidity and a side effect of medications: a systematic review and meta-analysis - Pan, Pei-Yin; Jonsson, Ulf; Çakmak, Sabriye Selin Şahpazoğlu; Häge, Alexander; Hohmann, Sarah; Norrman, Hjalmar Nobel; Buitelaar, Jan K.; Banaschewski, Tobias; Cortese, Samuele; Coghill, David; Bölte, Sven (Psychological medicine, 2022)
There is mixed evidence on the association between headache and attention-deficit/hyperactivity disorder (ADHD), as well as headache and ADHD medications. This systematic review and meta-analysis investigated the co-occurrence of headache in children with ADHD, and the effects of ADHD medications on headache. Embase, Medline and PsycInfo were searched for population-based and clinical studies comparing the prevalence of headache in ADHD and controls through January 26, 2021. In addition, we updated the search of a previous systematic review and network meta-analysis of double-blind randomized controlled trials (RCTs) on ADHD medications on June 16, 2020. Trials of amphetamines, atomoxetine, bupropion, clonidine, guanfacine, methylphenidate, and modafinil with a placebo arm and reporting data on headache as an adverse event, were included. Thirteen epidemiological studies and 58 clinical trials were eligible for inclusion. In epidemiological studies, a significant association between headache and ADHD was found [odds ratio (OR) = 2.01, 95% confidence interval (CI) = 1.63-2.46], which remained significant when limited to studies reporting ORs adjusted for possible confounders. The pooled prevalence of headaches in children with ADHD was 26.6%. In RCTs, three ADHD medications were associated with increased headache during treatment periods, compared to placebo: atomoxetine (OR = 1.29, 95% CI = 1.06-1.56), guanfacine (OR = 1.43, 95% CI = 1.12-1.82), and methylphenidate (OR = 1.33, 95% CI = 1.09-1.63). The summarized evidence suggests that headache is common in children with ADHD, both as part of the clinical presentation as such and as a side effect of some standard medications. Monitoring and clinical management strategies of headache in ADHD, in general, and during pharmacological treatment are recommended.